PERAN GURU AGAMA HINDU DALAM MENUMBUHKAN MINAT BELAJAR BIDANG STUDI PENDIDIKAN AGAMA HINDU DI SMP NEGERI I PERMATA KECUBUNG - Mardwiatmoko, Mardwiatmoko (Padma Sari: Jurnal Ilmu Pendidikan, 2024)
The purpose of this study is to find out the aspects that cause the lack of interest in learning of grade 9 students in the field of Hindu Religious Education at SMP Negeri I Permata Kekubung. This research is motivated by the phenomenon of many students who are often absent for various reasons that cannot be accounted for, ignoring the tasks given by teachers, low interest in reading and most of the students are passive in the teaching and learning process. This research is a case study research. The approach used in this study is qualitative. Data sources are obtained through observation, structured interviews, and documentation. In order to obtain data validity, the data source triangulation method is applied. Based on the results of the study, it was found that the aspects that caused the lack of interest in learning of students were internal aspects consisting of: students' ideals and low understanding of concepts in the field of Hindu Religious Education study, external aspects consisting of family economic status, the absence of support from parents that can support the improvement of students' religious knowledge, the lack of parental knowledge of Hindu teachings, and the state of the environment that does not reflect as a religious society. The results of the study also show that the teacher concerned has played a role in fostering the learning interest of grade 9 students in the field of Hindu Religious Education. Hindu Religious Education teachers can use the findings of this study as a guideline to make efforts to improve learning.